INFLUENCE OF PRICE, CELEBRITY AND PRODUCT QUALITY REGARDING SKINCARE PURCHASING DECISIONS FOR FEB UMSU STUDENTS - Maharani, Shalsyabila; Nasution, Satria Mirsya Affandy (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine and analyze the influence of price, celebrity and product quality on purchasing decisions for skincare products among FEB UMSU students, both partially and simultaneously. This research uses a quantitative approach, with multiple linear analysis techniques. The results of the research show that price has a significant influence on skincare purchasing decisions, partially Selebgram has a significant influence on skincare purchasing decisions, partially product quality has a significant influence on skincare purchasing decisions, simultaneously there is an influence of price, celebrity grams and product quality decisions on somethic skincare purchasing. The results of the regression calculations show that the coefficient of determination (R square) obtained is 0.434, this result means that 43.4% of the purchasing decision variables can be explained by the variables price, celebrity and product quality, while the remaining 56.6% is influenced by other variables not studied.